Economies of West Africa Region and the Environmental Kuznets Curve: Empirical Assessment - Leonard , Aisien N; David, Umoru (Asian Journal of Empirical Research, 2016)
This study examines the validity of the Environmental Kuznets Curve (EKC) in the developing economies of West Africa using a total of 32 cross sectional observations for each of the 16 countries of West Africa given a balance panel of 512 observations covering the periods 1980 through to 2012. The study estimated both the fixed effect and random effect model but however, the Hausman test shows that the estimates of the random effect are more consistent. The empirical results from this study provide evidence of the existence of the EKC for West Africa Countries as a group with income turning point ranging between US4,240.83 and US4,698.91. The study thus recommends that developing countries should not wait until they reach this high income turning point to reconcile economic growth and environmental improvement. The policy implication is that an induced environmental policy response is necessary for EKC to exist.